ヒョウショウ シンソウ クッサク ドリル ノ カイハツ II - 成田, 英器; ナリタ, ヒデキ; 藤井, 理行; フジイ, ヨシユキ; 高橋, 昭好; タハカシ, アキヨシ; 田中, 洋一; タナカ, ヨウイチ; 本山, 秀明; モトヤマ, ヒデアキ; 新堀, 邦夫; シンボリ, クニオ; et al. (1995)
P(論文) 南極深層コア掘削計画における深層掘削が1995年から1996年の2年間で行われる。この計画に使用する掘削装置の開発を1988年から行ってきた。掘削が行われるドームふじ観測拠点は, 平均温度-58.6℃, 標高3800mという掘削作業の環境として今までに無い厳しい場所であり, 昭和基地からは1000km離れている。そのため, 低温下での限られた人数での掘削作業, 物資輸送の面からも軽量で, 省力型の掘削システムの開発が要求された。掘削機として5つのタイプを考案し, これらについて実験を繰り返した。その中から2つのタイプを選び, 南極やグリーンランドにおけるフィールドテスト, そして掘削機各部の実験室内の実験から最良の機種を決定した。さらに, この実験用ドリルの完成度を高めるため, グリーンランド氷床や北海道陸別における15m氷柱を用いての掘削テストを繰り返し行った。本報告は, 低温・高圧切削, コアキャッチャー, 切削刃, バレル等の各部所に新しく考案した機構を盛り込んだ掘削機の完成までの過程を, 中間報告(藤井ら, 南極資料, 34,286,1990)に引き続き記したものである。 A deep ice coring system, which is to be used at Dome Fuji Station located at the summit of the Queen Maud Land ice sheet in 1995 and 1996,has been under development since 1988. The mechanical system was designed to reduce power consumption and weight. Many experiments were carried out on parts of the system in a cold laboratory. Simultaneously, field experiments of the drill system were done at Dome GRIP, Greenland ice sheet and at Rikubetsu, Hokkaido. As a result, a electro-mechanical drill which is simple both in shape and mechanism can be designed and produced incorporating many new ideas introduced through the experiments. departmental bulletin paper